Periodic Polymerization and the Generation of Polymer Giant Vesicles Autonomously Driven by pH Oscillatory Chemistry - Guo, Jinshan; Poros-Tarcali, Eszter; Pérez-Mercader, Juan (Frontiers in Chemistry, 2021)
Using the radicals generated during pH oscillations, a semibatch pH oscillator is used as the chemical fuel and engine to drive polymerization induced self-assembly (PISA) for the one-pot autonomous synthesis of functional giant vesicles. Vesicles with diameters ranging from sub-micron to 5 µm are generated. Radical formation is found to be switched ON/OFF and be autonomously controlled by the pH oscillator itself, inducing a periodic polymerization process. The mechanism underlying these complex processes is studied and compared to conventional (non-oscillatory) initiation by the same redox pair. The pH oscillations along with the continuous increase in salt concentration in the semibatch reactor make the self-assembled objects undergo morphological evolution. This process provides a self-regulated means for the synthesis of soft giant polymersomes and opens the door for new applications of pH oscillators in a variety of contexts, from the exploration of new geochemical scenarios for the origin of life and the autonomous emergence of the necessary free-energy and proton gradients, to the creation of active functional microreactors and programmable release of cargo molecules for pH-responsive materials.